Investigating the role of Lactococcus lactis D1813, salinity, and dissolved oxygen on the nutritional, chromatic, and textural profile of Litopenaeus vannamei - Muhammad Adil; Guo Xinbo; Junpeng Cai; Muhammad Waseem; Muhammad Faisal Manzoor; Crossby Osei Tutu (Food Chemistry: X)
The present study investigated the effect of L. lactis D1813, salinity (8 and 25 ppt), dissolved oxygen (8.5 and 3.5 mg/L), and freshwater shrimp reared in natural freshwater conditions (0 ppt salinity, ∼7.5 mg/L DO) without probiotic addition on its nutritional, chromatic and textural profile. Among the nutritional composition results, the highest protein, ash, and fiber contents were observed in the Huang group meat, i.e., 15.25, 4.50, and 3.99 g/100 g, respectively. Likewise, the results for the analysis of the mineral anticipated that the highest levels of K, Cu, Se, Fe, and Zn were found in Huang head group, i.e., 536, 6.3, 603, 9.2 and 4.6 mg/kg, respectively with high levels of astaxanthin, i.e., 270 μg/g. The Huang meat group also observed maximum chewiness and cohesiveness, i.e., 79.5 and 0.4, respectively. Furthermore, the results for amino acids elucidated the presence of the highest concentrations in the Huang meat group, such as isoleucine, valine, threonine, methionine, and arginine, i.e., 1.85, 1.33, 1.17, 1.44, and 1.33 g/100 g, respectively when compared with control. The highest levels of polyunsaturated fatty acids, such as eicosapentaenoic acid and docosahexaenoic acid, were observed in the Huang head group, i.e., 11.29 and 5.57 g/100 g. Our findings suggest that using L. lactis D1813 as probiotics along with the salinity and dissolved oxygen of 8 ppt and 7.5 mg/L significantly improves the nutritional profile of L. vannamei with better nutrient efficiencies. Furthermore, the study suggests probing the different probiotics in shrimp physiology, such as immune response and disease resistance.